Methicillin-Resistant Staphylococcus Aureus Nasal Carriers among Laboratory Technical Staff of Tertiary Hospital in Eastern Nepal - Neupane, R.; Bhatt, N.; Poudyal, A; Sharma, A. (Kathmandu University Medical Journal, 2020)
Background Methicillin-resistant Staphylococcus aureus (MRSA) has been the leading cause of nosocomial and community infections worldwide. In particular, healthcare workers are at constant risk to develop MRSA carriage. There is a paucity of data regarding the epidemiology of MRSA in laboratory workers who are constantly in contact with these pathogens in almost every hospital. Objective This study was undertaken to identify the burden of MRSA nasal carriers and the antibiotic susceptibility pattern of the isolates among laboratory technical staff. Method Sterile nasal swabs were taken from 50 laboratory technical staff working in the Central and Emergency laboratory of BP Koirala Institute of Health Sciences (BPKIHS). Standard procedures were followed for isolation, identification and antibiotic sensitivity testing. Antibiotic susceptibility tests were performed using disc diffusion and growth on Oxacillin screen agar based on Clinical and Laboratory Standards Institute (CLSI) guidelines. Result Out of 50 isolates of Staphylococcus aureus, 44 (88%) were Methicillin-sensitive (MSSA) while six (12%) were Methicillin-resistant (MRSA). All 50 isolates of S. aureus were found resistant to Penicillin while all were found sensitive to Teicoplanin, Linezolid, and Levofloxacin. Only five (10%) were sensitive to Erythromycin while 49 (98%) were sensitive to both Amikacin and Gentamicin. However, none of the MRSA isolates were found sensitive to all tested antimicrobial agents. Conclusion This repertoire portrays the emergence of MRSA in laboratory workers which clearly indicates the necessity of complying with the sanitary and antibacterial guidelines and adhering to the rational use of antibiotics to prevent nosocomial infections.